2014
DOI: 10.1063/1.4861852
|View full text |Cite
|
Sign up to set email alerts
|

An ab initio investigation of the ground and low-lying singlet and triplet electronic states of XNO2 and XONO (X = Cl, Br, and I)

Abstract: A systematic ab initio treatment of the nitryl halides (XNO2) and the cis- and trans- conformers of the halide nitrites (XONO), where X = Cl, Br, and I, have been carried out using highly correlated methods with sequences of correlation consistent basis sets. Equilibrium geometries and harmonic frequencies have been accurately calculated in all cases at the explicitly correlated CCSD(T)-F12b level of theory, including the effects of core-valence correlation for the former. Where experimental values are availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 96 publications
1
3
0
Order By: Relevance
“…The optimized structures of the five isolated molecules (INO, INO 2 , cis ‐IONO, trans ‐IONO, and IONO 2 ) are shown in Figure while their geometric parameters and corresponding vibrational frequencies are listed in the Supporting Information (Tables S1 and S2) together with the available literature data . The values of the geometric parameters are close to those previously obtained by Bailleux and coworkers for INO at the CCSD(T)‐F12b/cc‐pVQZ‐F12 level of theory, Papayannis and Kosmas for INO 2 , cis ‐IONO, trans ‐IONO, and IONO 2 at the B3LYP/LANL2DZ2df and MP2/LANL2DZ2df levels of theory, Peterson and Francisco for INO 2 , cis ‐IONO, trans ‐IONO at the CCSD(T)‐F12b/cc‐pVQZ‐F12 level of theory, Allan and Plane for IONO 2 at the B3LYP/6‐311 + G(2d,p) level of theory, and Kaltsoyannis and Plane at the B3LYP/aug‐cc‐pVTZ(+all electron basis for iodine atom) level of theory.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…The optimized structures of the five isolated molecules (INO, INO 2 , cis ‐IONO, trans ‐IONO, and IONO 2 ) are shown in Figure while their geometric parameters and corresponding vibrational frequencies are listed in the Supporting Information (Tables S1 and S2) together with the available literature data . The values of the geometric parameters are close to those previously obtained by Bailleux and coworkers for INO at the CCSD(T)‐F12b/cc‐pVQZ‐F12 level of theory, Papayannis and Kosmas for INO 2 , cis ‐IONO, trans ‐IONO, and IONO 2 at the B3LYP/LANL2DZ2df and MP2/LANL2DZ2df levels of theory, Peterson and Francisco for INO 2 , cis ‐IONO, trans ‐IONO at the CCSD(T)‐F12b/cc‐pVQZ‐F12 level of theory, Allan and Plane for IONO 2 at the B3LYP/6‐311 + G(2d,p) level of theory, and Kaltsoyannis and Plane at the B3LYP/aug‐cc‐pVTZ(+all electron basis for iodine atom) level of theory.…”
Section: Resultssupporting
confidence: 79%
“…There are only three experimental works for nitrosyl iodide (INO) and nitryl iodide (INO 2 ) using either Ar matrix or gas phase studies . The experimental values of the I‐N stretch (468 cm −1 ) and the out‐of‐plane bend (650 cm −1 ) for INO 2 are not consistent with the theoretical values (see reference for detailed discussion).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it would seem that the correlation contribution of ( n –1)­d, and perhaps ( n –1)­spd, electrons needs to be appropriately treated for an accurate benchmark. For calculations on bromine- and iodine-containing systems, core–valence corrections have been applied by several authors. That being said, it has recently been reported that contributions to bond energies from ( n –1)­sp correlation are typically an order of magnitude smaller than those from ( n –1)­d correlation …”
Section: Resultsmentioning
confidence: 99%
“…For calculations on bromine-and iodine-containing systems, core-valence corrections have been applied by several authors. [97][98][99][100] That being said, it has recently been reported that contributions to bond energies from (n-1)sp correlation are typically an order of magnitude smaller than those from (n-1)d correlation. 85 For the purpose of examining core-valence correlation contributions, we have chosen four complexes, namely (03) CH 4 …Br 2 , (04) CH 4 …I 2 , (35) HBr…CH 3 OH, and (36) HI…CH 3 OH as test systems; we then performed CCSD(T)/haVTZ,awCVTZ(Br,I) half-CP calculations for (i) valence electrons only, (ii) valence + (n-1)d electrons, and (iii) valence + (n-1)d + (n-1)sp electrons.…”
Section: Effect Of (N-1)d Electron Correlationmentioning
confidence: 99%